Nurses’ knowledge of the brain death adjudication procedure - Majchrowicz, Bożena (Journal of Education, Health and Sport, 2022)
Introduction: The issue of brain death is an extremely important puzzle for the world of medicine. Nursing care for a potential donor is considered a priority of the process, from the diagnosis of brain death to the donation and transplantation of the organ. The aim of the research was to assess the level of knowledge of nurses about the procedure of adjudication of brain death Material and methods: An online survey among 206 nurses associated on social networking sites. The research tool was the original questionnaire. Results and conclusions: Nursing care for a potential donor requires specialist knowledge and experience. The level of knowledge of the respondents about brain death and the applicable transplant law is not differentiated due to socio-demographic factors. The respondents have knowledge of the legal regulations in force in the area of ​​the death adjudication procedure.